Assessment of Agreement between Gated SPECT Myocardial Perfusion Imaging and Echocardiography for Measurement of Left Ventricular Parameters in Dilated Cardiomyopathy Patients (Bangladesh Journal of Nuclear Medicine, 2022)
Background: Left ventricular function, volumes and regional wall motion provide valuable diagnostic information and are of long-term prognostic importance in patients with dilated cardiomyopathy (DCM). This study was designed to assess the agreement between the 2D-echocardiography and gated single-photon emission tomography (SPECT) for evaluation of these parameters in patients with DCM.Patients and methods: Gated SPECT and 2D-echocardiography were performed in 60 patients having DCM. Gated SPECT data, including left ventricular volumes and left ventricular ejection fraction (LVEF), were processed using an automated algorithm. Standard technique was used for 2D-echocardiography. Regional wall motion was evaluated using both modalities and was scored by two independent observers using a 4-point scoring system for 5 specific walls.Results: The overall agreement between the two imaging modalities for the assessment of regional wall motion was 95% (286/300 walls). With gated SPECT left ventricular ejection fraction (LVEF), end-diastolic volume (EDV), and end-systolic volume (ESV) were 27.38±6.71%, 214.73±75.35 ml, and 158.33±63.22 ml, respectively, and 31.25±5.09%, 185.05±55.63 ml, and 123.47±46.00 ml, respectively, with echocardiography. The correlation between gated SPECT and 2D-echocardiography was moderate (r = 0.59, P